Typhoid Fever Surveillance and Vaccination Recommendations: WHO Eastern Mediterranean Region, 2021 - Yesser Sebeh; Ashley Longley; Muhammad Tayyab; Nandini Sreenivasan; Kashmira Date; Eric Mintz; Evans Buliva; Lucy Breakwell Nagle (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Annually, there are 5.57 to 9.23 million typhoid fever cases and 46,200 to 163,000 associated deaths, mainly in low- and middle-income countries. High incidence is estimated in the Southeast Asian, African, and Eastern Mediterranean (EMR) regions of the WHO. We reviewed EMR typhoid surveillance and vaccination recommendations to inform regional prevention and control efforts. Separate surveys were sent to surveillance and immunization officers in all 21 EMR countries and the occupied Palestinian territory, with 17 surveys (77%) and 13 surveys (59%) completed, respectively. Fifteen countries routinely collected typhoid surveillance data. Eleven countries (73%) used standard case definitions. Nine countries (53%) implemented health facility-based surveillance with laboratory confirmation. Five countries (33%) primarily used blood culture (the gold standard). Seven countries performed antimicrobial susceptibility testing, and two countries recommended typhoid vaccination. Strengthening typhoid and antimicrobial resistance surveillance is important to monitor burden and resistance trends and inform typhoid prevention and control measures.